Comprehensive identification of GSK3 gene family in celery and functional characterization of AgSK22 involvement in salt stress - Xinyue Guo; Lan Zhang; Qing Zhang; Xinyue Yan; Chunliu Zuo; Xiaoming Song; Min Yuan (Vegetable Research)
Plant glycogen synthase kinase 3 (GSK3) family members, as a class of serine/threonine protein kinases, have been demonstrated to play essential roles in a wide range of biological processes in many plant species. Here is the first study to report on the GSK3 gene family in celery (Apium graveolens). A total of 11 GSK3 genes were identified, phylogenetically classified into four subgroups, and accordingly unified as AgSKs, based on the classification and nomenclature of this gene family in Arabidopsis. The AgSKs from the same subgroup shared similar motif organizations. The critical motifs modulating the GSK3 kinase activity, CDFGSAK, SYICSR, TREE, and M/LEYV, were present and highly conserved across the whole AgSK family in celery. Whole-genome or segmental duplication significantly contributed to the expansion of the AgSKs. Cis-acting elements analysis and quantitative real-time PCR demonstrated the AgSKs were extensively involved in the plant response to cold, salt, and drought stresses, implying the potential essential functions of the AgSKs in celery. The transgenic Arabidopsis plants that overexpressing AgSK22 exhibited more sensitive to salt stress on seeds germination, suggesting that AgSK22 negatively regulated salt stress response. The results would provide guidance for functional characterizations of the AgSK genes in modulating the agronomic traits associated with abiotic stresses in celery.